Evaluating the relationship between lactate levels during coronary artery bypass graft surgery and postoperative renal dysfunction - Fatemehshima Hadipourzadeh; Roxana Rastravan; Ziae Totonchi; Evaz Heydarpur; Zahra Faritous (Journal of Cardiovascular and Thoracic Research)
Introduction: Postoperative Acute renal failure related to cardiac surgery is a common complication due to cardiac surgery and is estimated to influence up to 30% of patients. Serum lactate is a famous biomarker of tissue ischemia and is regularly checked during surgery. Methods: In this retrospective observational research, the records of 395 patients undergoing CABG were examined. Patients were classified into 4 groups based on the difference between the maximum lactate level measured during surgery and its baseline level. Also creatinine and urea levels, blood sugar, hemoglobin, and hematocrit pre, postoperative were recorded. The intraoperative and postoperative use of inotropes and the durations of surgery, cardiopulmonary bypass pump, and aortic cross-clamping were also recorded. Results: According to the results, pre, post and 24-hour postoperative blood urea nitrogen were not significantly related to intraoperative lactate changes. Also, pre and 24-hour postoperative creatinine had no significant relationship with intraoperative lactate changes, while postoperative creatinine was significantly associated with intraoperative lactate changes (P value=0.05). The duration of cardiopulmonary bypass (P value=0.02), intraoperative inotrope infusion (P value=0.03), inotrope infusion during the first six hours in ICU (P value=0.049), and receiving packed cell (P value=0.006) and receiving platelets during surgery (P value=0.04) were significantly related to intraoperative lactate changes. Furthermore, no significant relationship was observed between the duration of hospitalization in the ICU and the hospital and intraoperative lactate changes. Conclusion: According to the results, blood lactate level is an unreliable marker for predicting renal dysfunction postoperative.